การสื่อสารเพื่อประกอบสร้างอัตลักษณ์นักแข่งอีสปอร์ตในประเทศไทย - ศุภกฤตษ์ จิตตภัทราวงศ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2019)
The study "Communication for identity construction of E-sport competitors in Thailand" is a qualitive research; intended to, first, describe communicative ways E-sport competitors employ to shape their identities. Second, to describe communicative ways E-sport competitors employ when communicating with the public. Third, to describe competitors’ perceptions of their own identities. In doing so, researcher utilized 4 different research methodologies; In-depth Interview (with Thailand’s E-sport competitors, coaches, scholars, sponsors, etc.), Focus Group Interview, Non-participant Observation, and Document Analysis. The findings exhibited 2 channels of identity formation. First, through a Physical World by Definition, Appearance & Demeanor, Language, and Competitions. Second, through a Virtual World by Self Extension and Name Picking. The combination of both channels resulted in competitors’ complete identities and communicative ways to deconstruct, construct, and neutralize public generalization. In terms of public perceptions and interpretations, the results demonstrated that the public perceived competitors’ identities via Definition and Appearance & Demeanor regardless of specific place and time. In addition, varied degrees of interest accounted for different acceptance rates the public had toward competitors.